Andragogical Principles in Pre-Service Sports Coach Education for Adult Learners - Irmawita, Irmawita; Hayati, Ridha Husnul; Biru, Rembulan Catra Banyu; Azizah, Zahratul; Ilhami, Aldeva (Universitas Negeri Padang, 2024)
Andragogy is a set of ideas about how to help adults learn that have yet to get much attention in sports teaching, especially in schools that prepare people to become coaches. This qualitative exploratory study looked at a university program in Padang, Indonesia, that was meant to prepare students to work with adult athletes. The study looked at how the ideas from Knowles' Andragogy in Practice Model were used in that school. We talked to and asked 14 pre-service coaching students and nine adult players about their learning experiences, interests, and environmental factors. The results aligned with andragogy ideas like giving students choice, problem-based learning, and teaching based on values. Cultural values valuing group work and obedience to authority clashed with basic pedagogical principles. Economic limits also affected how ready people were to learn on their own. The general company mindset continued to be similar to how young people are coached. A combined method that adapts andragogy to the local social, cultural, and sports norms is offered to improve coaching education and adult learning in this setting. The results shed light on an area that has not been studied much and applied to andragogical theory. They also show how to use teach-ing methods appropriate for different cultures.